Surgical Management of Rhabdomyosarcoma of the Nasal Cavity and Paranasal Sinuses: Analysis of Operative Indications, Settings, and Outcomes - Kana, Lulia A.; Smith, Joshua D.; Bellile, Emily L.; Chugh, Rashmi; McKean, Erin L. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives The role of surgery in management of sinonasal rhabdomyosarcoma (SNRMS) has traditionally been limited, owing to anatomic and technological challenges and the established role of systemic therapy. Herein, we report our institutional experience with surgical management of SNRMS, with a particular focus on operative approaches, extent and outcomes.Design This study is a retrospective cohort study.Setting This study was conducted at a single-institution, academic center.Participants Patients of any age with histologically confirmed RMS of the nasal cavity, maxillary, ethmoid, frontal, or sphenoid sinus, nasolacrimal duct, or nasopharynx presenting between 1994 and 2020 were included in this study.Main Outcome Measures Demographics, tumor characteristics, operative settings, complications and recurrence, and survival outcomes were the primary outcomes of this study.Results Our study cohort comprised of 29 patients (mean [range] age: 27.0 [3.1–65.7], n = 12 [41%] female). Tumors of the nasal cavity (n = 10, 35%) and ethmoid sinuses (n = 10, 35%) and those with alveolar histology (n = 21, 72%) predominated. Patients who had surgery as part of their treatment (n = 13, 45%) had improved distant metastasis-free survival (DMFS) overall (hazard ratio [HR]: 0.32, 95% CI: 0.11, 0.98, p = 0.05) as compared with those who did not have surgery. Surgical approaches included open (n = 7), endoscopic (n = 4), and combined (n = 2). Eight of these 13 patients (62%) had an R0 resection. Additionally, surgical salvage of recurrent disease was employed in five patients (17%).Conclusion SNRMS is an aggressive malignancy with a high rate of recurrence and spread requiring a multidisciplinary approach for optimal outcomes. Our data supports an expanding role for surgery for SNRMS given its feasibility, tolerability, and potential to improve outcomes.
Keywords: rhabdomyosarcoma; surgery; paranasal sinus; nasal cavity; parameningeal; endoscopic; image guidance